Taking a punt: Monetary experimentation and the Irish macroeconomic crisis of 1955-56 - Darragh McLaughlin; Eoin McLaughlin; Seán Kenny (Heriot-Watt University, Department of Accountancy, Economics, and Finance, 2025)
The 1955-56 macroeconomic crisis is a central event in modern Irish history. Yet, despite this centrality, its causes are not clearly understood. In 1955-6, Ireland, which had previously followed British interest rates in lockstep as part of its fixed exchange with the latter, briefly experimented with independent monetary policy. Our contribution is twofold. First, we highlight how the Irish response was based on a misunderstanding of a run on Sterling in 1955. Second, we focus on a series of monetary shocks taking place from January 1955 to February 1956. We construct yields for Irish and UK public debt, as well as bank share indices at a daily frequency (1954-6), to test whether the shock was transmitted via financial markets. Employing an event study and testing for structural breaks, we explore the institutional framework through which the mechanisms of the crisis occurred. We find that expansionary monetary policy can only be maintained with sufficient reserves, merely postponing the inevitability of capital flight which is observed in the banking sector.
Keywords: E42; E52; F45; N14; N24; 330; Monetary Policy; Monetary Union; Optimum Currency Area; Trilemma